2016
DOI: 10.1037/pro0000090
|View full text |Cite
|
Sign up to set email alerts
|

Exploring parental divorce among emerging adult women: The roles of support networks and family relationships.

Abstract: What is the experience of parental divorce like when it takes place during emerging adulthood? A phenomenological study examined how parental divorce during emerging adulthood gives meaning to emerging adults' experiences, specifically with regards to support networks and familial relationships. Fifteen females between the ages of 18 and 25 (M ϭ 21.5) whose parents divorced after age 18 were interviewed. Three themes of meaning emerged from the data: emotional consequences of loss and contradictory coping, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…ACOD are erroneously thought to be largely unaffected by their parents' divorce due to their independence and ego maturity (e.g., Cooney, 1994;Greenwood, 2012). However, adult children, including our own participants, often report that parental divorce in adulthood is a serious emotional trauma (e.g., Cooney et al, 1986;Reed, Lucier-Greer, & Parker, 2016). In fact, over half of our participants (61%; n = 14) mentioned that seeking professional help, such as counseling, was an important tool for coping with parental divorce.…”
Section: Practical Applicationsmentioning
confidence: 91%
See 2 more Smart Citations
“…ACOD are erroneously thought to be largely unaffected by their parents' divorce due to their independence and ego maturity (e.g., Cooney, 1994;Greenwood, 2012). However, adult children, including our own participants, often report that parental divorce in adulthood is a serious emotional trauma (e.g., Cooney et al, 1986;Reed, Lucier-Greer, & Parker, 2016). In fact, over half of our participants (61%; n = 14) mentioned that seeking professional help, such as counseling, was an important tool for coping with parental divorce.…”
Section: Practical Applicationsmentioning
confidence: 91%
“…not only survive it [parental divorce] without scarring but to heal the wounds of their parents, a task too great to be achieved" (p. 200). Thus, adult children may engage in intense emotional labor to help their parents, while sacrificing their own self-care and coping (e.g., Greenwood, 2012;Reed et al, 2016). Clinicians should help ACOD learn how to communicatively establish and maintain boundaries regarding divorcerelated information management (Colapinto, 1991), even if it means upsetting the parent.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental divorce or separation can also have a negative effect on emerging adults' sibling relationships, with studies reporting lower levels of closeness and warmth between siblings in divorced families, compared to those in non-divorced or separated families (Conger and Little, 2010;Nitzburg, 2013;Milevsky, 2019). Yet, in a qualitative study of young adult women's experiences of parental divorce, Reed et al (2016) found that participants most often described turning to their siblings as a source of support during their parents' divorce, whereas comparatively few participants felt that discussing their needs with their parents during this time was helpful.…”
Section: Family Structurementioning
confidence: 99%
“…In an age of social media and ever prevalent internet distractions, it appears that emerging adults use more distraction and compartmentalization in their grief reactions. In their work with emerging adults who experienced the divorce of parents, authors noted coping isolation and tangible distractions as an effective short-term solution because it allowed them to avoid the pain and still manage their lives (Reed, Lucuer-Greer, & Parker, 2016). For millennials, this avoidance seems readily accessible.…”
Section: Emotional Instability and Unhealthy Copingmentioning
confidence: 99%